Hubungan antara Peer Attachment terhadap Perilaku Bullying pada Pelajar SMP di Kota Padang - Refin, M. Syukri Yusra (AHKAM, 2024)
Currently, bullying cases are one of the cases that often occur in the adolescent environment. Bullying cases are increasingly occurring in the world of education and causing various parties to be increasingly worried, including the KPAI or Indonesian Child Protection Commission. Many methods have been used to minimize bullying in the school environment, including one of which is from the National Commission for Child Protection urging schools to better protect and pay attention to their students. In this study, the sampling technique used a questionnaire distributed to research subjects at schools that had been previously determined by the researcher. The subjects in this study consisted of 261 students from different junior high schools in Padang City. The subjects of this study were taken based on the Isaac and Michael table with a 5% error rate. This study used a simple random sampling technique. A study has been conducted on the relationship between peer attachment and bullying behavior. The results show that peer attachment in junior high school students in Padang City is in the moderate category with a percentage of 44.4%, for bullying behavior it is in the low category with a percentage of 52.9%, and peer attachment and bullying behavior in junior high school students in this study have a low correlation of -0.128. In addition, peer attachment and bullying behavior are negatively related; if the relationship between peer attachment and bullying behavior is low, then bullying behavior will be low, and vice versa, if the relationship between peer attachment and bullying behavior is high, then bullying behavior will be high.